Comparative pharmacognostical investigation on four ethanobotanicals traditionally used as Shankhpushpi in India - Neeraj K Sethiya; Ashish Trivedi; Mayur B Patel; S H Mishra (Wolters Kluwer Medknow Publications, 2010)
People in Indian region often apply Shankhpushpi and other Sanskrit-based common name to Evolvulus alsinoides, Convolvulus pluricaulis, Canscora decussata, and Clitorea ternatea. These are pre-European names that are applied to a medicinal plant. Before the establishment of British rule, like the other books, ayurvedic treatises were also hand written. This might be one of the reasons due to which ayurveda could not stand parallel to the western medicine and an ambiguity is reflected in the interpretation of names and description of drugs found in the books like Charaka Samhita and Sushruta Samhita. The most widespread application of Shankhpushpi is for mental problems, but they have been considered for an array of other human maladies. The present investigation deals with the comparative pharmacognostical evaluation of four ethanobotanicals of Shankhpushpi. A comparative morphoanatomy of the root, stem, and leaves has been studied with the aim to aid pharmacognostic and taxonomic species identification. Various physicochemical, morphological, histological parameters, comparative high-performance thin-layer chromatography (HPTLC), and comparative high-performance liquid chromatography (HPLC), chromatogram of methanolic extract presented in this communication may serve the purpose of standard parameters to establish the authenticity of commercialized varieties and can possibly help to differentiate the drug from the other species. All the parameters were studied according to the WHO and pharmacopoeial guidelines.